PENGARUH MOTIVASI TERHADAP MINAT WIRAUSAHA PADA MAHASISWA STEIN - Aini Zahra; Bambang NS (LPPM Universitas Asa Indonesia, 2015)
Purpose- is to findout the effect of The Effect of Intrinsic And Extrinsic Motivation Against Enterpreneursip of student of STEIN. Design/methodology/approach- The respondents were selected purposively the stuent of STEIN. Data collected using quesionaire, and analyzed by multiple regression. Findings-It is concluded that Intrinsic And Extrinsic Motivation have positively effected Enterpreneurship of student in STEIN. Research limitations- The limited object of study and variable assigned in this research that can be extended in the future research. Practical implications- The scheme of student background and their intrinsic and extrinsic motivation can be blending by educators to be the spirit of entrepreneurship among the students of STEIN. The Originality-Usage of primary data as the basis of this research at a single college